A Study on Physico-chemical Charactersitics of Yamuna River around Hamirpur (UP), Bundelkhand Region Central India - Dhaka2, Minakshi3 and Chanchal1, Vinit Kumar1, *Sandeep Arya1, Anshu (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> River Yamuna, the largest tributary of River Ganga has been one of the most prominent and important rivers of India. Unfortunately, certain stretches of River Yamuna are very polluted. Various urban centers are located on the banks of Yamuna River, draw fresh river water for various activities. In almost the entire wastewater generated by these centers is disposed off into the river. The objective of the monitoring studies undertaken for water body is to assess variation in water quality with time. Ten sampling stations were selected along the river for sampling purpose from January to June, 2010.Water samples were analyzed in terms of physico-chemical water quality parameters. Range of values were found as temperature (14°C-28°C), pH (6.43-9.13), conductivity (340.00 µmhos -734.00 µmhos), DO (4.90 mg/l-8.50 mg/l), BOD (3 mg/l-8 mg/l), COD (11 mg/l-24 mg/l), alkalinity (123.00 mg/l- 240.00 mg/l), total hardness (230.00 mg/l- 475.00 mg/l), chloride (18 mg/l-32 mg/l) and fluoride (0.40 mg/l-1.20mg/l). The values of these parameters indicate that Yamuna River is moderately polluted under the study area.